The Hadith on Choosing a Life Partner: Analysis Ma'ani Al-Hadis and Social Criticism of Modern Marriage - Mirzan, Muhammad; Muhajirin, Muhajirin; Ghazali, Muhammad (STIT Sunan Giri Bima, 2026)
This study aims to analyze the meaning of the hadith of Prophet Muhammad (peace be upon him) concerning four factors considered in choosing a spouse: wealth, lineage, beauty, and religion. This research employs a qualitative approach using a library research method and the ma' ani al- ḥadīth analysis to examine both the textual and contextual meanings of the hadith. The findings indicate that the mention of these four factors in the hadith is descriptive of the social realities of society rather than a normative sequence that must be followed. The Prophet Muhammad explicitly directed Muslims to prioritize religious commitment as the primary criterion in selecting a life partner. The study demonstrates that religion and moral character serve as the fundamental foundation for building a harmonious and sustainable household. Academically, this research contributes to strengthening the contextual understanding of hadith and highlights its relevance in addressing the growing tendencies of materialism in contemporary marriage culture.